Policies for widening participation and success factors in Portuguese higher education - Martins, S. C.; Carvalho, H.; Ávila, P.; Costa, A. F. (Creative Education, 2017)
Portugal’s body of higher education students has progressively expanded, and opportunities for graduate certification at this level have multiplied. This paper advances factors that may provide a differentiated explanation of successful paths in higher education. It gives a first-hand account of the recent dynamics of participation in higher education in Portugal within the Bologna Process and uses institutional statistics to compare some of its most relevant characteristics with the European framework as a whole. Secondly, we used an extensive survey of Portuguese higher education students to identify factors potentially involved in successful paths and conducted a multiple logistic binary regression. The resulting model therefore included not only social and educational characteristics and backgrounds but also previous school trajectories, attendance of educational institutions and everyday practices. It identified key factors for success in academic careers by reference to a specific policy context and attendance of higher education. Our definition of these factors (dimensions of analysis) was based on the proposals of Tinto (2006; 1997) and Pinto (2002), using the variables available in that survey. Our results point to the relevance of institutional and educational dimensions as differentiated contexts of significance in different academic paths.